Determinants of Earnings Management in Indonesian Consumer Non-Cyclical Companies - Sari, Irma Novita; Muslimin, Muslimin (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to examine the effect of financial distress, profitability, and audit quality on earnings management in Indonesian consumer non-cyclical sector companies during the 2021–2023 post-pandemic period. Methodology: This research uses a quantitative approach with panel data regression based on 198 observations from 66 sample. The Fixed Effect Model (FEM) is selected as the best estimation model after Chow and Hausman tests. Classical assumption tests are also conducted. Results: The results show that financial distress, profitability, and audit quality simultaneously affect earnings management (Prob. F-statistic = 0,0000 < 0,05). However, only profitability has a significant positive effect (Prob. t-Statistic = 0,0050 < 0,05), while financial distress (Prob. t-Statistic = 0,2246) and audit quality (Prob. t-Statistic 0,4346) do not show significant influence. The adjusted R² is 0,4532, indicating that 45.32% of the variance in earnings management is explained by the model. Findings: Profitability is the only significant factor influencing earnings management, implying that higher profitability increases the tendency for earnings manipulation. Financial distress and audit quality do not significantly affect earnings management. Novelty: This study uniquely focuses on the post-pandemic consumer non-cyclical sector in Indonesia, a sector assumed to have stable demand but still experiences earnings volatility. Originality: By integrating three key determinants in a single empirical model and focusing on a specific post-crisis sector, this research offers new insights into earnings management behavior in relatively stable industries. Conclusion: The findings highlight that despite assumptions of stability in the consumer non-cyclical sector, managerial discretion in financial reporting still exists, particularly when profitability is high. These insights are valuable for investors, regulators, and auditors in evaluating financial statement reliability. Type of Paper: Empirical Research.